(untitled) (European Journal of Economics, Finance and Business Development, 2024)
Entrepreneurship’s pivotal role in economic growth and innovation is emphasized in Uzbekistan, where economic reforms are cultivating a robust landscape for small businesses. Regional dynamics, aligned with governmental insights and market mechanisms, foster entrepreneurship’s development, echoing the nation’s strategic goals. Successful initiatives in the Samarkand region highlight the symbiosis of internal growth drivers and international investments, shaping a promising entrepreneurial environment for sustained economic prosperity.